2018
DOI: 10.12705/671.7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships and generic reassessment of Proustia and allies (Compositae: Nassauvieae)

Abstract: Proustia is a small southern Andean genus of shrubs, vines and small trees, which are characteristic elements of Chilean and Argentine Andean forests, thickets and desert scrubs. Since Proustia possesses an unusual and characteristic morphology within the Nassauvieae, its circumscription as well as its phylogenetic placement is decisive in understanding the evolution of the tribe. Berylsimpsonia, from the Caribbean, was segregated from Proustia, which currently only includes three species. Lophopappus, another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Kelt et al (2000) showed high similarity of small mammal faunas within the wSADD, though no species were shared between the geographically extreme areas of the Atacama Desert and Patagonia, perhaps because the Andes act as a geographical barrier within the wSADD (see Ab'Sáber 1977, Luebert andWeigend 2014). While most of the endemisms are restricted to portions of it, several plant groups that occupy the entire wSADD are also present in other neighboring regions, such as Ephedra, (Ephedraceae; Ickert-Bond et al 2009), Leucheria (Asteraceae; Jara-Arancio et al 2017), Montiopsis (Montiaceae; Hershkovitz 2019), Nassauvia (Asteraceae; Grossi et al 2017) and Proustia (Asteraceae; Sancho et al 2018). Unlike the eSADD, it is questionable that the wSADD has acted as a corridor for arid adapted taxa.…”
Section: Biogeographic Patterns Within and Around The Dry Diagonalsmentioning
confidence: 99%
“…Kelt et al (2000) showed high similarity of small mammal faunas within the wSADD, though no species were shared between the geographically extreme areas of the Atacama Desert and Patagonia, perhaps because the Andes act as a geographical barrier within the wSADD (see Ab'Sáber 1977, Luebert andWeigend 2014). While most of the endemisms are restricted to portions of it, several plant groups that occupy the entire wSADD are also present in other neighboring regions, such as Ephedra, (Ephedraceae; Ickert-Bond et al 2009), Leucheria (Asteraceae; Jara-Arancio et al 2017), Montiopsis (Montiaceae; Hershkovitz 2019), Nassauvia (Asteraceae; Grossi et al 2017) and Proustia (Asteraceae; Sancho et al 2018). Unlike the eSADD, it is questionable that the wSADD has acted as a corridor for arid adapted taxa.…”
Section: Biogeographic Patterns Within and Around The Dry Diagonalsmentioning
confidence: 99%